Lighting controller based on PC serial port / Hermiza Abdullah Sani - Abdullah Sani, Hermiza (2006)
The main purpose of this project is to help users how to control their electrical appliances without go to each class to on or off and monitor breakage. This project focused on the developing lighting controller system in Windows platform. The lamp can be controlled through parallel port on Personal Computer (PC) by program developed using software for example Borland C. The lamp and the PC can be accessed and controlled via parallel port cable by a Web-based Lighting Controller program. Parallel port interface circuit was constructed for the purpose of the controlling the appliances. Basically the parallel port is to be used as a media interface in this controlling purpose. The parallel port is a very simple and affordable technique in controlling external circuitry.